Ventricular Tachycardia Originating from the Septal Papillary Muscle of the Right Ventricle: Electrocardiographic and Electrophysiological Characteristics. (5th November 2014) - SANTORO, FRANCESCO; DI BIASE, LUIGI; HRANITZKY, PATRICK; SANCHEZ, JAVIER E.; SANTANGELI, PASQUALE; PERINI, ALESSANDRO PAOLETTI; BURKHARDT, JOHN DAVID; NATALE, ANDREA
RV Septal Papillary Muscle VT Introduction Premature ventricular complexes (PVCs) and ventricular tachycardia (VT) arising from papillary muscles of both ventricles have recently been described. There is a lack of data on VT originating from the right ventricular papillary (RV PAP) muscles. There have been no prior studies focused on the electrocardiogram (ECG) features and ablation of PVC/VT arising from the septal papillary muscle of the right ventricle. Methods Among 155 consecutive patients with normal structural heart who underwent catheter ablation of PVC/VT, 8 patients with PVC/VT from the septal RV PAP muscle were identified. The site of origin of the arrhythmias was identified through activation/pace mapping and intracardiac echocardiography. All patients underwent radiofrequency ablation of the arrhythmia. Results Data on 8 consecutive patients (2 men, age 42 ± 13 years old) were collected. All patients had a preserved ejection fraction (60 ± 4%). Septal RV PAP arrhythmias had a left superior axis and negative concordance or late R‐wave transition in precordial leads. PVCs were spontaneous in 5 cases, were induced by isoprotenerol in 2 cases and by isoproterenol plus phenylephrine in another one. PVCs were never induced with calcium bolus and only rarely with burst pacing. Adenosine never terminated VT or suppressed the VT/PVCs. Radiofrequency, fluoroscopic, and procedural time were, respectively, 10.3 ± 3, 36.4 ±11.3, and 76.3 ± 27.5 minutes. During a mean follow‐up of 8 ± 4 months, mean PVC burden was reduced from 14 ± 3% preablation to 0.1 ± 0.2% postablation. Conclusion PVCs and VT originating from septal RV papillary muscle could have a typical ECG pattern due to the site of the muscle involved. Radiofrequency ablation of this anatomic area is feasible and effective.